First Costa Rican record of Pacific Golden-Plover (Pluvialis fulva, Gmelin, 1789) (Aves: Charadriidae) - Julio Sánchez; Johan Ramírez; César Sánchez (Check List, 2014)
Here we report on the first observation of Pacific Golden Plover in Central America, from Costa Rica. An individual in winter plumage was observed on salts ponds along with several other roosting waders